Management of Historical Tourism Objects in Supporting the Tourism Sector in Manado City, North Sulawesi Province - Ruru, Joorie M.; Plangiten, Novva N.; Palar, Novie R. A. (Journal La Bisecoman, 2024)
This study was conducted to identify and analyze the management of historical tourism objects in supporting the tourism sector in Manado City based on organizational aspects (the process of dividing tasks, authority, and resources). It is expected that through this study, forms and patterns of management of historical tourism objects will be found that can support the development of the tourism sector in Manado City. This study uses a qualitative method with a grounded research approach. Data were collected through interviews with managers of historical sites and heads of authorized agencies as well as national/foreign tourists who travel to Manado City. Observations were made by directly visiting historical sites in Manado City and collecting secondary data electronically using searches on Google Scholar/Google Scholar. The analysis technique was carried out by means of data reduction, data presentation and drawing conclusions and data verification. The findings of the study with the current form of management show that historical tourism objects have not become one of the aspects that support the tourism sector in Manado City.